Answer:
The result should be:
[tex](x-6)^2+(y-8)^2=\sqrt{65}[/tex]
Step-by-step explanation:
-The equation of a circle:
[tex](x-h)^2+(y-k)^2=r^2[/tex] where the center is [tex](h,k)[/tex], the point [tex](x,y)[/tex] and the radius known as [tex]r[/tex].
-Use the center (6,8) and the point (-1,4) for this equation:
[tex](-1-6)^2+(4-8)^2=r^2[/tex]
-Then, you solve for the radius and get the equation:
[tex](-1-6)^2+(4-8)^2=r^2[/tex]
[tex](-7)^2+(-4)^2 =r^2[/tex]
[tex]49 + 16 = r^2[/tex]
[tex]65 = r^2[/tex]
[tex]\sqrt{65} =\sqrt{r^2}[/tex]
[tex]\sqrt{65} = r[/tex]
-Result:
[tex](x-6)^2+(y-8)^2=\sqrt{65}[/tex]